From German to Yiddish: adaptation strategies in the Kuhbukh and the Siben weisen mainster bichel - Juillard-Maniece, J (2013)
In light of often derogatory and unqualified assessments of Yiddish literature adapted from German narrative models, this thesis will propose a different approach to viewing these adaptations. Building on methodologies and frameworks of analyses developed in contemporary medieval scholarship, this thesis pushes for a re-assessment of this literature and suggests a flexible model of adaptation that views adaptation as a creative interaction between two texts. In response to unsatisfactory approaches to judaizing strategies found in Yiddish texts adapted from German literature, this thesis also suggests a different approach. Judaizing processes can either be part of overall processes of adaptation aimed at coding the text as Jewish within an overarching framework of renewed cultural specificity; or, they can function as translation principles by achieving equivalence with the original model. To illustrate both ends of this scale of adaptation, this thesis centres on two early modern Yiddish texts: the Kuhbukh (Verona, 1595) and the Siben weisen mainster bichel (Basel, 1602). The four chapters at the core of this thesis develop and apply extensive frameworks of literary analyses which enable us to rigorously assess the differing levels of adaptations (translation and Wiedererzählen) of both texts. This thesis pushes for a future reassessment of other popular Yiddish narratives adapted from German models. This could ideally be achieved by a positioning of each individual Yiddish text based on German narratives on the proposed scale of adaptation. This should be backed by verifiable methodologies and analyses devoid of unjustifiably dismissive opinions. This would consequently move scholarship towards structured, methodological analyses of early Yiddish secular literature.